Phcog Rev. is now in PUBMED - KK, Mueen Ahmed (Pharmacognosy Reviews)
On behalf of Pharmacognosy Reviews (Phcog. Rev.) and editorial team, I am pleased to announce our recent acceptance for indexing in PubMed—an official database of US National Library of Medicine (NLM) for the scientific and technical quality of articles published in our journal. PubMed is one of the indexing services and are archived on PubMed Central, the NLM’s comprehensive online archive of nearly 2 million full-text articles.[1]Phcog. Rev. started in 2007 is one of its kind publishing exclusively, high quality reviews in the field of pharmacognosy.[2] The ability to find Phcog. Rev.’s articles through PubMed literature searches will make it easier for both researchers and readers to find, assess, and read them. Indexing by the NLM and accessibility through PubMed Central provide enhanced visibility and easier access to articles.